2017
DOI: 10.1016/j.ymthe.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-218-5p as a Potential Target for the Treatment of Human Osteoarthritis

Abstract: Emerging evidence suggests that dysregulated microRNAs (miRNAs) play a pivotal role in osteoarthritis (OA), but the role of specific miRNAs remains unclear. Accordingly, we identified OA-associated miRNAs and functional validation of results. Here, we demonstrate that miR-218-5p is significantly upregulated in moderate and severe OA and correlates with scores on a modified Mankin scale. Through gain-of-function and loss-of-function studies, miR-218-5p was shown to significantly affect matrix synthesis gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 39 publications
1
39
1
Order By: Relevance
“…Our previous studies have shown that dysregulated miR-98 and miR-193a-3p were involved in IDD 10 , 51 . In addition, our recent study demonstrated that inhibition of endogenous miR-218-5p expression/activity appears to be an attractive approach to OA treatment 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that dysregulated miR-98 and miR-193a-3p were involved in IDD 10 , 51 . In addition, our recent study demonstrated that inhibition of endogenous miR-218-5p expression/activity appears to be an attractive approach to OA treatment 52 .…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the Ras/Erk and PI3K/AKT signaling pathways often promotes cancer cell growth and metastasis as well as enhances chemoresistance by inducing c-Myc-mediated cell cycle and EMT signaling. [47][48][49][50][51] Based on Funrich analysis, 52 these two pathways were screened as potential signals affected by miR-296-3p. We confirmed that miR-296-3p suppresses Ras/Erk and PI3K/AKT signals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the dysregulation of miR-140-3p and miR-140-5p in synovial fluid correlates with the severity of OA [ 16 ]. miR-218-5p is a novel inducer of cartilage destruction via modulation of PI3K/Akt/mTOR signaling, inhibition of endogenous miR-218-5p expression/activity appears to be an attractive approach to OA treatment [ 17 ]. Recent study has described that miR-15a-5p promotes the degeneration of chondrocytes by targeting parathyroid hormone-related protein and may be a potential biomarker of OA [ 18 ].…”
Section: Introductionmentioning
confidence: 99%